Congenital Rubella Syndrome Screening for Newborn in Yogyakarta, Indonesia - Triono, Agung; Candrawati, Oktania; Sudarman, Kartono; Intansari, Umi Sholekah; Haksari, Ekawaty Lutfia; Soenarto, Srisupar Yati; Herini, Elisabeth Siti (Journal of Pediatric Infectious Diseases, 2018)
Background Rubella infection in pregnancy can cause congenital rubella syndrome (CRS), and one common defect of CRS is hearing loss. However, hearing screening is not routinely performed in Indonesia. While the number of reported cases of CRS in Indonesia is increasing, it is still difficult to identify all CRS cases. This study aims to identify CRS cases through a newborn hearing screening.Materials and Methods This descriptive study was conducted at Dr. Sardjito Hospital, Yogyakarta, Indonesia. The subjects were recruited from September 1, 2013 to November 19, 2013. The study period was from September 1, 2013 to January 31, 2014. Newborn subjects underwent the first otoacoustic emissions (OAEs) test. Subjects with the first OAEs test REFER results underwent the second OAEs test 2 months later. Subjects with REFER result in the second OAEs test then underwent auditory brainstem response (ABR) and detection of rubella IgM in blood serum.Result There were 151 subjects who underwent the first OAEs test. Ninety subjects (60%) had REFER results, but only 29 subjects underwent the second OAEs test. In the second OAEs test, 9/151 (5%) subjects were REFER. There were 6/151 (3.9%) subjects who underwent ABR and all subjects had sensory neural hearing loss. Of them, one subject was positive for rubella IgM with a titer of 11.86 at 2.5 months of age. We found nine suspected CRS cases, one clinically-confirmed and one laboratory-confirmed CRS case. The incidence of laboratory-confirmed CRS was 1/151 (6.62/1,000) live births.Conclusion Due to the low incidence we found and the cost of screening, we recommend to strengthen surveillance of CRS. All infants less than 1 year of age with suspected CRS should be checked with rubella IgM to identify CRS cases. While universal newborn hearing screening is not mandatory in Indonesia, targeted newborn hearing screening should be performed to detect children with permanent congenital hearing loss due to CRS.
Keywords: congenital rubella syndrome; newborn; screening; hearing loss